Effects of Lemuru Fish Oil, Fe, Zn, and Cr Supplementation on Performance, Blood Profile, and Organ Development of Sentul Chickens - Marsha Adinda Aurelia; Rita Mutia; Sumiati Sumiati; Rizky Nadia (Buletin Peternakan, 2026)
This study aimed to evaluate the effects of diet containing Lemuru fish oil supplemented with iron (Fe), zinc (Zn), and chromium (Cr) on growth performance, blood profile, and internal organ development in Sentul chickens, a native Indonesian breed. There were four experimental diets following a completely randomized design (CRD), each with five replicates and ten chickens per repetition, namely T0 (Control), T1 (diet containing 2.5% Lemuru fish oil), T2 (diet containing 2.5% Lemuru fish oil + 20 ppm Fe, 60 ppm Zn, 0.4 ppm Cr), and T3 (diet containing 2.5% Lemuru fish oil + 40 ppm Fe, 120 ppm Zn, 0.8 ppm Cr). Feed and water were provided ad libitum for 84 d. Parameters measured included body weight gain, feed intake, feed conversion ratio, Income Over Feed Cost, relative organ weights, intestinal length and, blood profile. Treatments did not significantly affect growth performance (p>0.05), with body weight at 84 d ranging from 905.70 to 962.93 g/b, feed intake ranging from 2958.15 to 2999.03 g/b and feed conversion ratio between 3.15 and 3.54. Hematological analysis revealed significant effects on erythrocyte and leukocyte counts, as well as lymphocyte percentage, with the highest erythrocyte count in T2 (2.83 × 106/µL) and the highest lymphocyte proportion in T1 (51.76%). Most internal organ weights did not differ significantly, except for the proventriculus. In summary, Lemuru fish oil with Fe, Zn, and Cr supplements did not adversely affect growth performance. When used at moderate dosages, the combination of fish oil and trace minerals improved economic values through IOFC, erythrocyte count, enhanced intestinal development, and immune characteristics, providing information on feeding strategies for native poultry.